The Effect of Proposed Exercises In Reducing The Proportion of Constant and Variable Errors in Tennis Flat Serve - Hussein, Loai (Journal of Physical Education, 2016)
The importance of the study lies in preparing exercises that help reduce the proportion of constant and variable error performance and develop the accuracy of performing the serve. The problem of the research lies in weakness in serving performance and the lack of serving performance accuracy. Moreover, the researchers have found instability in the results of attempts. This was due to focusing their training on the development of accuracy, without identifying the error found in performance. The subjects were (5) juniors tennis players aged (9 – 13). The main experiment consisted of 6 weeks with two sessions per week. Then, the posttest was conducted and the results of the study show that there is a significant difference between the pre and posttests in reducing the proportion of error. Finally, the researchers recommended adapting constant and variable errors for correct diagnosis and treatment of errors in performance.